Physiological and Molecular Characterization of Hydroxyphenylpyruvate Dioxygenase (HPPD)-inhibitor Resistance in Palmer Amaranth (Amaranthus palmeri S. Wats.) - Nakka, S.; Godar, A. S.; Wani, P. S.; Thompson, Curtis R.; Peterson, Dallas E.; Roelofs, Jeroen; Jugulam, Mithila (My University, 2017)
Herbicides that inhibit hydroxyphenylpyruvate dioxygenase (HPPD) such as mesotrione are widely used to control a broad spectrum of weeds in agriculture. Amaranthus palmeri is an economically troublesome weed throughout the United States. The first case of evolution of resistance to HPPD-inhibiting herbicides in A. palmeri was documented in Kansas (KS) and later in Nebraska (NE). The objective of this study was to investigate the mechansim of HPPD-inhibitor (mesotrione) resistance in A. palmeri. Dose response analysis revealed that this population (KSR) was 10-18 times more resistant than their sensitive counterparts (MSS or KSS). Absorbtion and translocation analysis of [C-14] mesotrione suggested that these mechanisms were not involved in the resistance in A. palmeri. Importantly, mesotrione (>90%) was detoxified markedly faster in the resistant populations (KSR and NER), within 24 hours after treatment (HAT) compared to sensitive plants (MSS, KSS, or NER). However, at 48 HAT all populations metabolized the mesotrione, suggesting additional factors may contribute to this resistance. Further evaluation of mesotrione-resistant A. palmeri did not reveal any specific resistance-conferring mutations nor amplification of HPPD gene, the molecular target of mesotrione. However, the resistant populations showed 4- to 12-fold increase in HPPD gene expression. This increase in HPPD transcript levels was accompanied by increased HPPD protein expression. The significant aspects of this research include: the mesotrione resistance in A. palmeri is conferred primarily by rapid detoxification (non-target-site based) of mesotrione; additionally, increased HPPD gene expression (target-site based) also contributes to the resistance mechanism in the evolution of herbicide resistance in this naturally occurring weed species.
Citation: Nakka, S., Godar, A. S., Wani, P. S., Thompson, C. R., Peterson, D. E., Roelofs, J., & Jugulam, M. (2017). Physiological and Molecular Characterization of Hydroxyphenylpyruvate Dioxygenase (HPPD)-inhibitor Resistance in Palmer Amaranth (Amaranthus palmeri S. Wats.). Frontiers in Plant Science, 8, 12. doi:10.3389/fpls.2017.00555
Keywords: Mesotrione; Resistant Mechanism; Target-Site; Non-Target-Site; Metabolism; Absorption And Translocation